2006
DOI: 10.1002/hipo.20177
|View full text |Cite
|
Sign up to set email alerts
|

Myristoylated alanine rich C kinase substrate (MARCKS) heterozygous mutant mice exhibit deficits in hippocampal mossy fiber-CA3 long-term potentiation

Abstract: The myristoylated alanine-rich C kinase substrate (MARCKS) is a primary protein kinase C (PKC) substrate in brain thought to transduce PKC signaling into alterations in the filamentous (F) actin cytoskeleton. Within the adult hippocampus, MARCKS is highly expressed in the dentate gyrus (DG)-CA3 mossy fiber pathway, but is expressed at low levels in the CA3-CA1 Schaffer collateral-CA1 pathway. We have previously demonstrated that 50% reductions in MARCKS expression in heterozygous Marcks mutant mice produce rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 92 publications
0
23
0
Order By: Relevance
“…In addition, MARCKS is involved in cell adhesion, lamellipodia formation, initiation of neuritogenesis, neurite outgrowth, growth cone adhesion, pathfinding, dendrite branching, dendritic spine morphogenesis, and synaptic plasticity (13,28,39,41,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). Knockdown of MARCKS by RNA interference and overexpression of MARCKS mutants revealed that non-phosphorylated MARCKS stabilizes growth cone adhesion, enhances branching and growth of dendrites, elongates dendritic spines, and enhances initiation of neuritogenesis and neurite outgrowth (65,66,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MARCKS is involved in cell adhesion, lamellipodia formation, initiation of neuritogenesis, neurite outgrowth, growth cone adhesion, pathfinding, dendrite branching, dendritic spine morphogenesis, and synaptic plasticity (13,28,39,41,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). Knockdown of MARCKS by RNA interference and overexpression of MARCKS mutants revealed that non-phosphorylated MARCKS stabilizes growth cone adhesion, enhances branching and growth of dendrites, elongates dendritic spines, and enhances initiation of neuritogenesis and neurite outgrowth (65,66,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…At sites of cell adhesion, vinculin plays a role in physiological processes such as cell motility, migration, development, and wound healing (42). Loss of normal vinculin function has been associated with invasive cancer phenotypes, cardiovascular disease states, and derangements in embryogenesis that are also present in the embryonic lethal MARCKS knock-out mouse (9,11,42,43). Importantly, the tail domain of vinculin binds to acidic phospholipids, predominantly PIP 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the phosphorylation of MARCKS has been implicated in neuronal development (5,9) and in the migration of vascular endothelial cells (7,12) and neurons (14). The MARCKS null knock-out mouse is embryonic lethal (9,11,13), and no tissue-specific mouse knock-out models have been described. Much about the receptor-dependent modulation of MARCKS phosphorylation and its implications for vascular cell function remains incompletely understood.…”
mentioning
confidence: 99%
“…Cytosolic myristoylated alanine-rich C kinase substrate (MARCKS) is phosphorylated by activation and translocation of many members of the PKC family, including PKC-θ (40). Therefore, to specifically test whether the fatty acids are impacting downstream targets of PKC-θ, we determined that i.c.v.…”
Section: Figurementioning
confidence: 99%